Pengaruh Model Pembelajaran Direct Instruction Terhadap Hasil Belajar Teknik Dasar Senam Lantai di SMAN 1 Klari - Islami Tefa, Muhamad Zidan Syahdilla; Abduloh, Abduloh; Kurniawan, Feby (Jurnal Ilmiah Wahana Pendidikan, 2023)
In the implementation of floor gymnastics learning activities in schools, student behaviors are often found that are not in accordance with expectations. Students feel afraid, hesitant and embarrassed to do the gymnastic movements taught by the teacher. The behavior of students who are afraid and hesitant when starting to do movements, students are afraid of being laughed at and made fun of when doing movements and have an impact on students losing their confidence, physical state. Lack of strength and flexibility is one of the inhibiting factors in gymnastics learning activities, the talents of students are very different, some learn quickly and some are slow. This type of research is experimental research. Experimental research is a study in which at least one variable is found that is manipulated to study cause-and-effect relationships. The research conducted was a pre-experimental study, with a research design in the form of "the one group pretest-posttest design". With this, it can be said that the direct instruction learning model has a significant influence with a scale of 8.89. After that, for the back roll, a different average score was obtained between the pre-test and post-test, namely the average score of the initial test of 63.81 and the average value in the final test of 76.15. With this, it can be said that the direct instruction learning model has a significant influence with a scale of 12.34.there is a difference between the results of learning floor gymnastics for pre test and post test, so that it can be concluded that there is an influence of the use of the direct instruction learning model on the learning outcomes of basic floor gymnastics techniques at SMAN 1 Klari.